The Space-Temporal Continuity of the Andalusian Urbanism in the Mudéjar Tradition - Duperré, Gustavo Norberto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
The influence of Al-Andalus, not only leaves its mark on the Mediterranean world, but also extended to urbanism and cultural ways in America, after the events of the Conquest. The buildings in New Spain and Quito (Ecuador) were, in part, the repositories of the crossings and influences of the Mudejar tradition in Spanish America, as consequence of that territorial and historical continuity. In this context, the Mendicant Orders embodied these new contributions in religious architecture. This provided a renewed appearance to the covers, internal spaces and roofs of the temples and convents, mainly.